REPRESENTASI PENGETAHUAN SECARA VISUAL: KAJIAN TERHADAP ORANG TUNANETRA DAN PEMECAHAN MASALAH MATEMATIKA SOAL CERITA - Hendra Kartika; Siti Mutmainah (Jurnal Kajian Pembelajaran Matematika, 2019)
Examining visual representations of knowledge, generally speaking of imagery or mental imagery. In recent years, mental imagery through visual representation in mathematical problem solving is still an interesting study to be explored. However, studies on the implications of visual representation of blind people have received much less investigative attention. In this paper, we will investigate three factors that address the goal of this review and to present some of the prominent questions for future research: 1) format of visual representation; 2) mental imagery on the congenital blindness; and 3) visualization on mathematical word problem-solving. Results indicate that the visual representation of knowledge is very substantially used to communicate various types of knowledge that describe relationships or patterns. Mental visualization between congenitally blind and sighted people qualitatively similar, but this results only on visuospatial skills. The results also indicate that visual representation can be used as a tool to solve mathematical word problems. For further study, this result proposes how the mental imagery of blind people can solve the mathematical problems (e.g. geometry, statistics) through visualization.